FORMING INCLUSIVE DESIGN PRODUCTS THROUGH ARTISTIC STYLES - Bulatov, Valery (Theory and practice of design, 2025)
The conducted research showed how different aesthetic styles – as holistic design philosophies – can be purposefully used to create inclusive design products. The purpose of the article is to analyze the processes of forming inclusive design products through the use of different stylistic approaches that can be purposefully used to achieve inclusive goals, while improving visual perception and emotional response. Methodology. Through the use of such analysis methods as systematization, comparison, complex analysis and generalization, the study successfully formed the main definitions of the topic and outlined the prospects for the influence of artistic styles on the creation of inclusive products. Results. It was demonstrated how the choice of a certain style not only ensures accessibility, but also significantly improves the visual perception and emotional response of users, making inclusivity an integral part of aesthetic perfection. The scientific novelty lies in creating the first comprehensive classification and systematization of methods for forming inclusive design precisely through the prism of aesthetic styles. The analysis presented how thoughtful and aesthetically appealing design is a guarantee not only of functional accessibility, but also of psycho- emotional well-being, self-identification and a sense of inclusion for users with disabilities. The study allowed for a deeper understanding of which aspects of style are key to creating inclusive design products. The conducted study helped to better understand how aesthetic style is key in shaping an inclusive environment, allowing products not only to perform functions, but also to give users psycho-emotional comfort, promote their self-identification and a sense of full social integration. The practical significance of the results obtained provides designers and developers with specific strategies and practical tools that allow them to transform the concept of inclusivity into real products that are accessible and convenient for each user. Conclusions. The study found that an attractive and thoughtful design style significantly expands the range of potential users. When assistive technologies – from wheelchairs to hearing aids, from prosthetics to inclusive software interfaces – are designed with an emphasis on elegance, modernity, and organic integration into everyday aesthetic spaces, they cease to be “special” or “medical” objects, but instead become inconspicuous, desirable, and even fashionable elements that harmoniously complement the user’s lifestyle.